The Premier versus the Aristocrat: Francis Hincks, John G. Vansittart, and Voters in the Oxford-General Election of 1851 - Emery, George; Emery, J.C. (Ontario History, 2008)
The authors use anecdotal evidence and cliometric methods to revisit the 1851 Oxford-general election. They open with the setting — the electoral process, the electorate, the voter turnout, the candidates, and the local issues: railway politics, radical democracy, and establishment religion. Then through analysis of voters, they investigate why Hincks — the incumbent, the province’s co-premier in the Hincks-Morin administration (1851–4), but also a non-resident — prevailed over Vansittart — the prominent, eldest son of the deceased Vice-Admiral Henry Vansittart. The central finding is that establishment religion, and in particular the clergy reserves, was the decisive issue in Oxford, with Vansittart and Hincks offering alternative middle-ground positions between the ultra-Tory and ultra-Reform extremes. The contrasting religious and ethnic traditions of the riding’s 2,500 voters gave Hincks a narrow win.